FIELD STUDY, ACTION PLAN AND E-COLLABORATION: TRANSFORMING EFFECTIVE INFORMATION SECURITY TRAINING PROGRAM FOR LOCAL GOVERNMENT IN INDONESIA - Ma’ruf, Kholif Faiz; Setyowati, Anik (PEOPLE: International Journal of Social Sciences, 2018)
Changing the bad paradigm of information security in 514 local governments in Indonesia is very challenging. The root of the problem must be found, and with limited resources, the right solution should be found to allow the solution to run across 514 local governments. FGD method is used to find the root of the problem, and the result is found that the main problem lies in the lack of competence and motivation of Information Security HR working in the Local Government. Although education and training have been provided to improve their competence, the fact that once they return to their workplace, they can not implement the science in their workplace. The second root of the problem is the absence of a quick and inexpensive consultation container to solve various problems. The author tries to address the root of the first problem through changes in the basic information security training curriculum in the form of a field study approach and an action plan. The root of the second problem is solved with cheap and effective online group collaboration, we call it a chain of hope. The training curriculum is being applied to 40 local governments by 2017 and the results are staggering. In the context of education, it is very difficult to see the outcome quickly, but based on our case study, just within 6 months after the training, the outcomes of the training can be seen in real terms. Now in every local government whose human resources have undergone basic information security training in the year 2017, will see the results of its work in the form of information security posters, antivirus already installed, awareness runs with innovative techniques, and the preparation of information security activities can already run. Based on these case studies, it can be assured that the information security in every local government in Indonesia has a good future if it starts with an appropriate Education Curriculum.